From zero to hero: the spatio-temporal patterns and migration influence mechanism of world-class athletes in China - Shi, J.; Li, G.; Xue, S.; Nie, Q. (Heliyon, 2022)
At present, China is in an important stage of transition into a global sports power where "outstanding competitive sports talents" are required to play an important role. Therefore, it is of great theoretical and practical significance to conduct in-depth research on domestic "outstanding competitive sports talents" to promote the sustainable development of China's competitive sports and enhance its comprehensive strength. In this study, WCA refers to "world-class athletes," indicating a group of talents who won medals in international sports events such as the Olympic Games during 2009-2019. In this regard, this study uses statistical and spatial analysis methods to reveal the spatial and temporal characteristics, evolutionary process, and migration mechanism of Chinese WCA. The conclusion shows that: In terms of temporal characteristics, the population numbers in general and among different genders are characterized by a "three peaks and two troughs" pattern. In contrast, the individual temporal pattern is characterized by an "inverted U" and "inverted V", with an average age of 23.18 years. In terms of space, a positive correlation is shown on the whole (Moran's I > 0), however, characteristics of geographical proximity and spatial heterogeneity are not prominent, illustrating the spatial form of random distribution with low aggregation which is primarily concentrated in the southeast of China and demonstrates a "northeast-southwest" trend. There are apparent differences between areas of origin and immigration areas: Liaoning and Shandong are the main areas of origin while destination areas are frequently located in the southeast and "People's Liberation Army of China" (PLA for short). Lastly, this paper discusses the causes and influences of the migration groups from three aspects: the migrating talents, the areas of origin and immigration areas, and Chinese sports, revealing the formation and influence mechanisms.